2020
DOI: 10.1177/1354816620934908
|View full text |Cite
|
Sign up to set email alerts
|

The impact of tourism growth on income inequality: Evidence from developing and developed economies

Abstract: In this article, we investigate the effects of tourism indicators on income inequality (IIE) in a sample of 102 countries. We divide the sample countries into 71 developing and 31 advanced economies. Using annual data from 1995 to 2014, we employ panel unit root tests, cointegration, fixed-effects, fully modified ordinary least squares, and causality techniques. Our findings show that tourism indicators have a significant negative impact on IIE in developing economies, while they have an insignificant impact i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
52
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(62 citation statements)
references
References 29 publications
7
52
3
Order By: Relevance
“…an (2) environmental effects including creating green and recreational areas, stimulating the restoration of industrial heritage and conservation of natural resources, etc. These results are opposite to the findings in [14][15][16][17].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…an (2) environmental effects including creating green and recreational areas, stimulating the restoration of industrial heritage and conservation of natural resources, etc. These results are opposite to the findings in [14][15][16][17].…”
Section: Discussioncontrasting
confidence: 99%
“…In addition, a study by [13] analysed the creative industry and demonstrated that boosting the creative industry had a positive impact on tourism development. At the same time, [14] analysed 102 countries and proved that tourism development had a significant impact on increasing income inequality in developing countries and an insignificant impact in developed countries. In [15], the negative impact of tourism visitors on CO 2 emissions was confirmed.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In line with the standard inequality literature, we use the Gini coefficient to measure the inequality variable (Fang et al, 2020; Folarin & Adeniyi, 2019; Fosu, 2015; Kaulihowa & Adjasi, 2018; Nguyen et al, 2020; Tchamyou et al, 2019a, 2019b). As argued by Fang et al (2020), the Gini coefficient is the best indicator—it is calculated based on the disposable income of the selected countries. Following the study by Alvarado et al (2017b), FDI inflows are used in this study.…”
Section: Methodsmentioning
confidence: 99%
“…Using Chinese data over the period of 2005-2010, Asadullah et al [27] suggest the potential of policies that reduce urban-rural income inequality in boosting well-being. Using a sample of 102 countries, Fang et al [28] find that international tourism improves income equality in developing economies, but has an insignificant impact in developed economies. Using data from Chinese provinces, Shi et al [29] find that inbound international tourism is negatively correlated with urban-rural income gap.…”
Section: Literature Reviewmentioning
confidence: 99%